2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition Workshops (CVPRW) 2019
DOI: 10.1109/cvprw.2019.00322
|View full text |Cite
|
Sign up to set email alerts
|

Crop Lodging Prediction From UAV-Acquired Images of Wheat and Canola Using a DCNN Augmented With Handcrafted Texture Features

Abstract: Lodging, the permanent bending over of food crops, leads to poor plant growth and development. Consequently, lodging results in reduced crop quality, lowers crop yield, and makes harvesting difficult. Plant breeders routinely evaluate several thousand breeding lines, and therefore, automatic lodging detection and prediction is of great value aid in selection. In this paper, we propose a deep convolutional neural network (DCNN) architecture for lodging classification using five spectral channel orthomosaic imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…allowing variations in color to potentially contribute more informative features for modelling [20,26]. Results in our study suggest that NAS generated models (AutoML) can provide very competitive performance compared to modern human designed CNN architectures.…”
Section: Image Regressionmentioning
confidence: 82%
See 2 more Smart Citations
“…allowing variations in color to potentially contribute more informative features for modelling [20,26]. Results in our study suggest that NAS generated models (AutoML) can provide very competitive performance compared to modern human designed CNN architectures.…”
Section: Image Regressionmentioning
confidence: 82%
“…showed that the AutoKeras model had a much higher number of predictions exceeding the maximum value of 100 (n=39), with the largest predicted value being 118 whereas the ResNet-50 model only have one prediction exceeding 100 with a value of 100.29 ( Figure 10). This would likely explain why the MAE score, which is the average of the absolute difference between predicted scores and actual learning [26]. The higher classification accuracies reported in that study may be due to the use of image data augmentation (i.e.…”
Section: Image Regressionmentioning
confidence: 85%
See 1 more Smart Citation
“…The high morbidity and considerable healthcare cost associated with cancer has inspired researchers to develop more accurate models for cancer detection. Over the last five years, data mining and machine learning models have been used in a variety of research areas to dramatically improve our ability to discover emergent patterns within large datasets [3]- [8]. Developing computer-aided diagnosis (CAD) systems, integrated with medical image computing and machine learning methods, has become one of the major research paradigms for life-critical diagnosis [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, developing accurate and reliable approaches for Leukemia detection is important for early treatment. Numerous study results showed that with the advancement of computational capabilities, hidden trends, patterns and relationships can be discovered using the application of data mining approaches in many different areas [5]- [8]. described in the subsequent sections.…”
Section: Introductionmentioning
confidence: 99%